Pelatihan Pembuatan Kecambah Kacang Hijau (Tauge) Dengan Media Pasir Sungai Untuk Masyarakat Dusun Banopo, Kabupaten Timor Tengah Utara - Emilia Juliyanti Bria; Yuni Sine; Risna Erni Yati Adu; Hermina Manlea; Dicky Frengky Hanas; Lukas Pardosi; Elisabeth Korbafo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
The people of Dusun Banopo mostly work as farmers who produce a variety of agricultural products. One of the products produced is mung beans. The yield of bean sprouts is very good and plentiful, however the utilization of this product is still very low, especially in supporting family health and increasing family income. Most of the produce is sold immediately and a quarter of the harvested are usually left at home to be cooked with corn. Mung bean seeds can be germinated into bean sprouts which have a higher nutritional content and can be used as marketed products. This service activity was well received by the community, especially the women from the Women Farmers Group. This group gains knowledge and skills in making bean sprouts with media that can be taken from the surrounding environment. Besides being able to be used as a nutritious vegetable in improving family health, it can also marketed to increase family income.